2013
DOI: 10.1029/2012jd018039
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of surface and vertical profile of aerosol properties over a tropical urban station Hyderabad, India

Abstract: [1] One year measurement of vertical profiles of volume backscatter and extinction coefficient, aerosol optical depth (AOD), mass concentration of black carbon (BC) and composite aerosol along with thermodynamic structure of the atmosphere has been carried out over an urban tropical location of Hyderabad(17.47 N, 78.58 E), India, during April 2009 to March 2010. The mean mixing layer height (MLH) exhibits large seasonality exceeding 4 km in pre-monsoon period whereas in winter it comes down tõ 1.5 km with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 133 publications
(188 reference statements)
4
21
0
Order By: Relevance
“…The study reported that the AOD of elevated aerosol layer could go as high as 0.25 in severe aerosol loading conditions [ Niranjan et al , ]. Sinha et al [] have reported 25% contribution from elevated aerosol layer (above 3.5 km) over Hyderabad during premonsoon, 2009–2010. In another study using MPL, 40–60% contribution of aerosol above 1.0 km during March 2005 were reported over Bangalore [ Satheesh et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…The study reported that the AOD of elevated aerosol layer could go as high as 0.25 in severe aerosol loading conditions [ Niranjan et al , ]. Sinha et al [] have reported 25% contribution from elevated aerosol layer (above 3.5 km) over Hyderabad during premonsoon, 2009–2010. In another study using MPL, 40–60% contribution of aerosol above 1.0 km during March 2005 were reported over Bangalore [ Satheesh et al , ].…”
Section: Resultsmentioning
confidence: 99%
“…At Zhangye station in northwest China, aerosol extinction coefficients in the upper and lower layers decreased with altitude, whereas the coefficient in the middle layer changed slightly, which suggested that aerosol mixing occurred in the middle layer (Zhang et al, 2012a). Sinha et al (2013) found that aerosols within atmospheric boundary layer (ABL) over a tropical urban station Hyderabad, India dominated the column aerosol loading with ABL-AOD, contributing not less than 50 % throughout the year. Over urban locations in South India, BC mass loadings decreased approximately monotonically from the surface to an altitude of 7 km (Safai et al, 2012).…”
Section: Xu Et Al: Similarities and Differences Of Aerosol Opticamentioning
confidence: 99%
“…Over Hyderabad, vertical profile of aerosol particles have been investigated by researchers using aircraft and balloons experimentation in campaign mode (Babu et al, 2011. Sinha et al (2013) used one year in-situ lidar observations to study the aerosol vertical distributions. They found that the ABL aerosols contribute from a minimum of 43.0% to a maximum of 97.9% to the total AOD.…”
Section: Vertical Distribution Of Aerosols Over Hyderabadmentioning
confidence: 99%
“…Vertical profile of ABC calculated following an inversion technique (Klett, 1985) by assuming a constant lidar ratio. However we have assumed different lidar ratios for each season by following Sinha et al (2013). Rayleigh vertical profile is calculated by using real time vertical profile observations of temperature and pressure from descending pass (~01:30 LT) of Atmospheric Infrared Sounder (AIRS) over the study location.…”
Section: Seasonal Variations Of Aerosol Backscatter Coefficient (Abc)mentioning
confidence: 99%